Sulfur transformation in coal during supercritical water gasification. (15th December 2016) - Meng, Nan; Jiang, Dandan; Liu, Yang; Gao, Zhiyuan; Cao, Yaqin; Zhang, Jinli; Gu, Junjie; Han, You
Graphical Abstract: Highlights: A modified method is used to test the sulfur forms in char. FeS2 transforms into Fe1 − x S, FeS and Fe3 O4 after coal SCW gasification. Liquid S after coal pyrolysis is S + 4 and S + 6, while S − 2 also exists in SCW case. Supercritical water restricts thiophene and SO2 forming. Abstract: The efforts of supercritical water (SCW) on sulfur transformation during coal gasification process were studied in a batch autoclave. Sulfur morphological distribution of two different rank coals on solid, liquid and gas phase at different temperatures were thoroughly investigated during coal SCW gasification compared with coal pyrolysis. Compared with coal pyrolysis, the removal of sulfate-sulfur and pyritic-sulfur in solid state were enhanced during coal SCW gasification, especially with temperature rising. Both in coal pyrolysis and coal SCW gasification, the XRD analysis showed that the pyrite which blended with coal transformed into pyrrhotite, whereas pyrrhotite further converted into magnetite during SCW gasification. Supercritical water had the ability not only restrict thiophene forming, but also oxidize organic-sulfur to produce sulfone, causing that the forming of organic-sulfur was restrained. The sulfate and sulfite were the main liquid-sulfur composition after coal pyrolysis, whereas sulfide also existed in spite of sulfate and sulfite after coal SCW gasification. The sulfide may be produced via H2 S absorbing in water. Because the sulfide can be oxidized into sulfate and sulfite by OH radicals in SCW condition, the amount of sulfate and sulfite was much larger than that after coal pyrolysis. The gas sulfur after coal pyrolysis included H2 S and SO2, but the abundant H radicals provided by SCW system caused much more H2 S produced and inhibited the formation of SO2 . The sulfur transformation could be explained by free radical mechanism. Those transformation properties were important for further environmental evaluation and the better using of coal SCW gasification technology with low sulfur pollution.